Analisis Efektivitas Transmisi Kebijakan Moneter Melalui Instrumen Syariah dan Konvensional Dalam Memengaruhi Inflasi di Indonesia - Nur Ariani Aqidah; Ishak Ishak; Takdir Takdir; Mutmainnah Azzahra (Owner : Riset dan Jurnal Akuntansi, 2022)
This research analyze the transmission of monetary policy through the syariah instrument and conventional instrument in influencing inflation in Indonesia with data analysis techniques using the Vector Error Correction Model. The data used in the research obtained from the 2016-2020 Indonesian Economic and Financial Statistics annual report, 2016-2020 Consumer Price Index data from Central Bureau of Statistics, the 2016-2020 Banking Statistics annual report and the 2016-2020 Islamic Banking Statistics annual report. The test results on the syariah instrument indicators show that the Consumer Price Index gives a negative response to shocks that occur in FINC and SBIS, while the Consumer Price Index gives a positive response to shocks that occur in DPK and PUAS. The test results on the conventional instrument indicators show that the Consumer Price Index gives a negative response to shocks that occur in LOAN, DPK and SBI, while the Consument Price Index gives a positive response to shocks that occur in PUAB. And the results of the Forecast Error Variance Decomposition test show that the influence of indicators from the syariah instrument variable simultaneously in influencing the Consumer Price Index as a proxy for inflation is greater than the indicators from the conventional instrument variable.